THE INFLUENCE OF ESG PERFORMANCE REPORTING ON FIRM VALUE IN INDONESIA - Afnei Ngan Billy Tumba; Gracia Alya Quina Akhmad; Dinda Ayu Sieradianto Angelia; Besse Nur Fatimah Hefri; Ananda Fadia Indah Ramadhani (Jurnal Riset Manajemen dan Bisnis, 2024)
ABSTRACT The implementation of strong Environmental, Social, and Governance (ESG) practices can improve efficiency, lower costs, increase productivity, and drive innovation, thus encouraging companies to expand into sectors with high growth potential. This is due to the increased efficiency, cost reduction, productivity boost, and innovation driven by robust ESG practices. This study aims to evaluate the impact of ESG performance on corporate value in Indonesia. The methodology employed in this research includes purposive sampling for sample selection, classical assumption tests, and multiple linear regression analysis for hypothesis testing. The research sample consists of companies listed on the Indonesia Stock Exchange (IDX) from 2019 to 2023 that have ESG scores. The main findings of this study indicate that ESG performance has a positive effect on corporate value. The conclusions drawn from this research provide valuable insights for companies in Indonesia regarding the implementation of ESG practices in their business operations to enhance corporate value. Keywords: Environmental Social and Governance; Return on Asset; Price to Book Value; Sustainability ABSTRAK Penerapan praktik Environmental, Social, and Governance (ESG) yang kuat dapat meningkatkan efisiensi, menurunkan biaya, meningkatkan produktivitas, dan mendorong inovasi, sehingga mendorong perusahaan untuk berekspansi ke sektor-sektor yang memiliki potensi pertumbuhan yang tinggi. Hal ini dikarenakan adanya peningkatan efisiensi, pengurangan biaya, peningkatan produktivitas, dan inovasi yang didorong oleh praktik ESG yang kuat. Penelitian ini bertujuan untuk mengevaluasi efek kinerja ESG terhadap nilai perusahaan di Indonesia. Metode yang diterapkan dalam penelitian ini mencakup purposive sampling untuk pemilihan sampel, uji asumsi klasik, dan analisis regresi linier berganda untuk pengujian hipotesis. Sampel penelitian terdiri dari perusahaan yang terdaftar di Bursa Efek Indonesia (BEI) dari tahun 2019 hingga 2023 yang memiliki skor ESG. Temuan utama penelitian ini menunjukkan bahwa kinerja ESG memiliki dampak positif terhadap nilai perusahaan. Kesimpulan dari penelitian ini memberikan wawasan yang signifikan bagi perusahaan-perusahaan di Indonesia mengenai penerapan praktik-praktik ESG dalam operasi bisnis mereka untuk meningkatkan nilai perusahaan. Kata kunci: Environmental Social and Governance; Return on Asset; Price to Book Value; Keberlanjutan